Causal Relationship Between Migraine and Postpartum Depression: A Two-Sample Bidirectional Mendelian Randomization Study - Zhou XJ; Chen R; Niu YM (Journal of Pain Research)
Xian-Jin Zhou,1,2,* Rui Chen,3,* Yu-Ming Niu4,5 1School of Gongli Hospital Medical Technology, University of Shanghai for Science and Technology, Shanghai, People’s Republic of China; 2Department of Anesthesiology, Shanghai First Maternity and Infant Hospital, Tongji University School of Medicine, Shanghai, People’s Republic of China; 3Department of Stomatology, Taihe Hospital, Hubei University of Medicine, Shiyan, People’s Republic of China; 4Department of Stomatology, Gongli Hospital of Shanghai Pudong New Area, Shanghai, People’s Republic of China; 5Administrative Office, School of Gongli Hospital Medical Technology, University of Shanghai for Science and Technology, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yu-Ming Niu, Department of Stomatology, Gongli Hospital of Shanghai Pudong New Area, Shanghai, People’s Republic of China, Tel +86 13581370999, Email niuyuming@yeah.netBackground: The possible causative relationship between migraine and postpartum depression (PPD) is examined in this study. Prior research has shown a strong correlation between the two conditions, but the exact cause is unknown.Methods: A bidirectional Mendelian randomization (MR) approach was employed to assess causality, utilizing discovery and replication samples from publicly available genome-wide association study (GWAS) datasets. Causal effects were estimated using the inverse-variance weighted (IVW) method, MR-Egger regression, and three additional MR approaches. Sensitivity analyses, including tests for heterogeneity, horizontal pleiotropy, and leave-one-out analysis, were conducted to evaluate the robustness of the findings.Results: Overall, no significant causal effect of migraine on PPD risk was identified in either the discovery (IVW: OR=1.018; 95% CI=0.928– 1.117; P=0.706) or replication analysis (IVW: OR=2.097; 95% CI=0.328– 13.409; P=0.434) in forward MR analysis. Similarly, no causal effect of migraine on PPD was observed in female-only analyses. Moreover, reverse MR analysis found no significant causal effect of PPD on migraine risk in discovery (IVW: OR=1.036; 95% CI=0.999– 1.075; P=0.057) or replication (IVW: OR=1.001; 95% CI=1.000– 1.002; P=0.274) analysis, and no causal effect was observed in female-only analyses. No evidence of heterogeneity or horizontal pleiotropy was detected in sensitivity tests.Conclusion: The current MR study indicates no significant causal relationship between migraine and PPD.Keywords: migraine, postpartum depression, Mendelian randomization, causal effect